ANALISIS PEMANFAATAN AIR CUCIAN BERAS SEBAGAI PENGKAYA PROBIOTIK KOMERSIL PADA MEDIAKULTUR UNTUK PENINGKATAN PERTUMBUHAN POPULASI Daphnia magna - Muhammad haqqul yaqin; Farikhah Farikhah; Ummul Firmani (Jurnal Perikanan Pantura (JPP), 2024)
This research aims to determine the formulation of probiotic feed fermented with rice washing water with different fermentation times to produce the highest growth of Daphnia magna. The research included experimental research using a Completely Randomized Design (CRD) consisting of 3 treatments and repeated three times to obtain nine experimental units. Each container is filled with 2 liters of water with a Daphnia density of 20 ind/l. Treatment A: giving probiotics and rice washing water without fermentation; treatment B: giving probiotics and rice washing water with a fermentation time of 6 hours; treatment C: giving probiotics and rice washing water with a fermentation time of 12 hours. Based on research conducted for 12 days, the results showed that the fermentation time of probiotics and rice washing water affected the population density of Daphnia magna. Treatment C: Giving probiotics and rice washing water with a fermentation time of 12 hours is the best treatment compared to other treatments.